Energy and carbon budgeting of traditional land use change with groundnut based cropping system for environmental quality, resilient soil health and farmers income in eastern Indian Himalayas. (1st September 2021) - Ansari, M.A.; Saha, Saurav; Das, Anup; Lal, R.; Das, Bappa; Choudhury, B.U.; Roy, S.S.; Sharma, S.K.; Singh, I.M.; Meitei, Ch Bungbungcha; Changloi, Kl Levish; Singh, L. Somendro; et al.
Abstract: Energy intensive traditional cereals based monoculture often lead to high greenhouse gas emissions and degradation of land and environmental quality. Present study aimed at evaluating the energy and carbon budget of diversified groundnut ( Arachis hypogea L) based cropping system with over existing traditional practice towards the development of a sustainable production technology through restoration of soil and environmental quality and enhancement of farming resiliency by stabilizing farmers' income. The trials comprised of three introduced groundnut based systems viz. groundnut– pea ( Pisum sativum ), groundnut–lentil ( Lens esculenta ) and groundnut–toria ( Brasssica campestris var. Toria) replacing three existing systems viz. maize ( Zea mays L) – fallow, maize – toria, and rice ( Oryza sativa L)-fallow systems. Four years study revealed that adoption of groundnut based systems reduced non-renewable energy input use (fertilizers, chemical, machinery and fossil fuels) by 25.5%, consequently that reduced the cost of production. Repeated analysis of variance measurement also affirmed that groundnut based systems (groundnut-pea>groundnut-lentil> groundnut-toria) increased the energy use efficiency, energy productivity, carbon use efficiency, net returns and decreased the specific energy and energy intensiveness. Groundnut based systems increased the mean system productivity and water productivity in terms of groundnut equivalent yield by 3.7 and 3.1 folds over existing practice. The savings of fossil fuel reduced greenhouse gas emissions owing to reduced use of farm machinery and synthetic fertilizers. Groundnut based systems significantly ( p < 0.05) enhanced the soil carbon concentration (8.7–18.1%) and enzymatic activities (27.1–51.8%) over existing practice. Consequently, estimated soil quality index values were 35.9–77.3% higher under groundnut based systems than existing practice. Thus, the study indicated the resilient nature of groundnut based systems as an environmentally safe and sustainable production technology for enhancing resource use efficiency, reduce carbon emission, energy intensiveness and cost of production in the Eastern Himalaya region of India and similar ecosystems. Graphical abstract: Image 1 Highlights: GBCS enhanced system productivity, returns and soil health over existing rice and maize based systems. GBCS enhanced water productivity, energy and carbon use efficiency over existing system. GBCS reduced carbon foot print and energy intensiveness over the existing rice/maize based system. GBCS increased soil quality index values by 44.2–60.0% over existing farmer's practice.